2015
DOI: 10.1017/jns.2015.14
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism, health and fillet nutritional quality in Atlantic salmon (Salmo salar) fed diets containing n-3-rich microalgae

Abstract: Microalgae, as primary producers of EPA and DHA, are among the most prominent alternative sources to fish oil for n-3 long-chain PUFA in animal and human nutrition. The present study aimed to assess technical, nutritional and fish health aspects of producing n-3-rich Atlantic salmon (Salmo salar) fish fillets by dietary supplementation of increasing levels of a DHA-producing Schizochytrium sp. and reduced or without use of supplemental fish oil. Atlantic salmon smolt were fed diets with graded levels of microa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
72
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 75 publications
12
72
1
4
Order By: Relevance
“…The TGC values in the present experiment were higher than those obtained by Sørensen et al [15], but were in the same range as reported by Hatlen et al [26]. Feed conversion rate was in line with studies performed on yeast- or microalga-fed Atlantic salmon of sizes comparable to that used in the present study [26, 27]. The dry matter intake (for each kg wet weight gain) of fish fed the highest inclusion level of defatted N .…”
Section: Discussionsupporting
confidence: 90%
“…The TGC values in the present experiment were higher than those obtained by Sørensen et al [15], but were in the same range as reported by Hatlen et al [26]. Feed conversion rate was in line with studies performed on yeast- or microalga-fed Atlantic salmon of sizes comparable to that used in the present study [26, 27]. The dry matter intake (for each kg wet weight gain) of fish fed the highest inclusion level of defatted N .…”
Section: Discussionsupporting
confidence: 90%
“…For R. salina, which contains significant percentages of both DHA and EPA and is used as aquaculture feed (e.g., Gagné et al 2010), this would imply that although the total cellular amount of fatty acids is higher, the nutritional value of this species is lower at the end of the growth phase. Currently, several microalgal species are being investigated by the aquaculture industry as fish meal or fish oil replacement in the diet of commercially farmed fish (Kousoulaki et al 2015;Sprague et al 2015;Sørensen et al 2016). Replacing the traditional EPA-and DHA-rich, but finite, marine ingredients, fishmeal and fish oil present a significant challenge for the aquaculture industry (Sprague et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Promising fish oil alternatives are lipids from microalgae which can potentially grow at high growth rates and which can reach high maximum cell densities with high levels of EPA and/or DHA. Much research has been focused on heterotrophic DHA-producing species such as Schizochytrium (Kousoulaki et al 2015;Sprague et al 2015). However, Sprague et al (2015) showed that the absence of EPA in Schizochytrium-based fish diet significantly impairs the overall nutritional value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An enzyme responsible for nitric oxide synthesis, called inducible nitric oxide synthase (iNOS) is the key protein in intestinal immunity, as it controls inflammatory cytokines such as TNFα (Kousoulaki et al . ). The enzyme regulates both the baseline mucus production in the gut, thus mitigating the damage to the intestinal mucosal lining due to inflammatory diseases (Schreiber et al .…”
Section: Chlorella Vulgaris In Fish and Crustaceans Immunitymentioning
confidence: 97%